Toddlers' Self‐Recognition and Progression From Goal‐ to Emotion‐Based Helping: A Longitudinal Study. Issue 4 (19th August 2019) - Aitken, Jess; Ruffman, Ted; Taumoepeau, Mele
Abstract : Research has typically used cross‐sectional designs to draw conclusions on the development of helping. This study aimed to examine the development of instrumental and empathic helping behaviors as they emerge, and assess how self‐recognition might moderate this progression. Seventy‐two children (14‐ to 25‐months at T1) were assessed over four monthly sessions. Participants' individual response patterns showed instrumental helping to be a necessary precursor to empathic helping for 55.77%–67.92% of children who helped during the study. Self‐recognition emerged before empathic but not instrumental helping, yet did not directly influence helping behavior.